Letter : National Joint Committee for Spanish Relief and Basque Children's Trust - Chester, George
1943-01-29 038-0020-002 NATIONAL UNION OF BOOT AND SHOE OPERATIVES Affiliated to the English, Irish & Scottish Trades Union Congresses & National Labour Party. Approved under the National Health Insurance Acts Approval No 281 and the Unemployment Insurance Acts Code No 245 GENERAL PRESIDENT LEN. SMITH GENERAL SECRETARY GEO. CHESTER THE GRANGE EARLS BARTON, NORTHAMPTON TELEPHONE: EARLS BARTON 327 29th January, 1943. GC/KN. Mr. H.V. Tewson, The Trades Union Congress, Transport House, Smith Square, London, S.W. National Joint Committee for Spanish Relief and Basque Children's Trust. Dear Mr. Tewson, My E.C. at their last meeting had before them a letter from the above Committee, in which the continued responsibility of the Committee was outlined, and appealing for financial assistance. I was unable to inform the Council of the present position of the Committee, or of their responsibilities, and I was, therefore, authorised to obtain, if possible, such information as was now available. I do not want to write direct to the Committee themselves, and I wondered if you had any knowledge of their present position, and if so, if you could advise me thereon. Faithfully yours, Geo Chester General Secretary. 292/946/38/20(II)